Application of Mucuna pruriens pellets, organominerals and Trichoderma harzianum agents in coffee seed beds (Coffea arabica) (Agroindustrial Science, 2026)
The excessive use of chemical fertilizers in agriculture has degraded soil quality, reduced fertility and caused environmental problems such as nutrient leaching. In response, regenerative practices are being explored to restore soil health and promote sustainable farming. This study evaluated the effects of nutrient-rich pellets made from Mucuna pruriens L., coffee husk-derived organominerals, monoammonium phosphate (MAP), and the biocontrol fungus Trichoderma harzianum Rifai on coffee seedlings (Coffea arabica). Conducted in a greenhouse in Tarrazu, Costa Rica, the experiment used eight treatments with twenty replicates each. The most effective formulation, 60% M. pruriens, 20% organominerals, and 20% MAP, applied at 100 – 150 g per plant, significantly improved seedling growth, nutrient uptake, microbial respiration, and plant survival. This mix also showed favorable chemical properties, including high nitrogen and phosphorus levels, near-neutral pH, and a low carbon-to-nitrogen ratio, enhancing nutrient availability. The addition of T. harzianum contributed to effective root disease control and was compatible with organic matter. Overall, the study highlights these pellets as a sustainable, multifunctional solution for plant nutrition and disease management in coffee nurseries, with potential applications in other crops. Further research is needed to evaluate their economic viability and potential for commercial use.
Keywords: pellets; Mucuna pruriens; organominerals; nutrients; microbial biomass